Characteristics of Modified Timor White Corn Flour and its Cookies Enriched with Moringa Leaves - Medho, Maria Susana; Mohamad, Endeyani Vivitrida (The University of Lampung, 2024)
Composite flour consisted of local Timor white corn and moringa leaf flours are rich in protein, crude fiber and dietary fiber but are relatively limited in use as ingredients for making cookies. This study aims to determine the characteristics of modified local Timor white corn flour and moringa leaves and their composite flour on the physico-chemical characteristics and sensory acceptance of corn cookies fortified with moringa. The research was conducted experimentally with 5 treatments on the proportion of corn flour to moringa flour, including F0 (100: 0), F1 (99:1), F3 (97:3), F5 (95:5), F7 (93:7). The results showed that the proportion of F7 composite flour have start time gelatinization 8.53 minute faster than the other formulation, and not significantly different from F3 and F5 but significantly different from F1 and F0. There was a significant decrease in the peak, final, hot paste, breakdown, and setback viscosity values, due to the fortification of moringa leaf flour. The difference in the proportion of corn and moringa leaf composite flour had no significant effect on sensory values texture, taste and smell but had a very significant effect on cookies color. The flour formulations F3, F5, and F7 produced cookies with higher protein, crude fiber and other dietary fiber values and had fulfilled the cookies requirements according to SNI 2973:2011. Keywords: Composite flour, Fortification, Pasting characteristics, Organoleptic test, Preferences.